Laminin 211 inhibits protein kinase A in Schwann cells to modulate neuregulin 1 type III-driven myelination - Ghidinelli, Monica (PLoS Biol, 2017)
Myelin is required for proper nervous system function. Schwann cells in developing nerves depend on extrinsic signals from the axon and from the extracellular matrix to first sort and ensheathe a single axon and then myelinate it. Neuregulin 1 type III (Nrg1III) and laminin α2β1γ1 (Lm211) are the key axonal and matrix signals, respectively, but how their signaling is integrated and if each molecule controls both axonal sorting and myelination is unclear. Here, we use a series of epistasis experiments to show that Lm211 modulates neuregulin signaling to ensure the correct timing and amount of myelination. Lm211 can inhibit Nrg1III by limiting protein kinase A (PKA) activation, which is required to initiate myelination. We provide evidence that excessive PKA activation amplifies promyelinating signals downstream of neuregulin, including direct activation of the neuregulin receptor ErbB2 and its effector Grb2-Associated Binder-1 (Gab1), thereby elevating the expression of the key transcription factors Oct6 and early growth response protein 2 (Egr2). The inhibitory effect of Lm211 is seen only in fibers of small caliber. These data may explain why hereditary neuropathies associated with decreased laminin function are characterized by focally thick and redundant myelin.